A Study in the Viability of Butea monosperma Seeds - Modi, Anupama; Kandya, Anand (International Journal of Scientific Research in Biological Sciences, 2017)
Tetrazolium testes are employed to evalute seed viability so as to achieve faster as well as reliable results. The Tetrazolium Test involves the use of 2, 3, 5, triphenyl tetrazolium chloride which in a living cell is reduced by the dehydrogenase enzyme system. This reaction yields a red compound called triphenyl formazan. Since this reaction is enzyme mediated the cell in which it is taking place has to be a liveing cell. Stained areas of a tissue in this test indicate occurrence of live cells and unstained ones the necrotic tissue. Thus, the test is considered very reliable to locate living cells. In evaluation of seed viability occurrence of a definite proportion of necrotic tissue to that of live tissue helps to the seed will germinate or not.